ANALYSIS OF THE SALES VOLUME ON BUSINESS INCOME: STUDY AT THE ISLAMIC BOARDING SCHOOL - Imam Zamrozi; Sugiono Sugiono; Rinnanik Rinnanik; Evi Novitasari (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the effect of sales volume on business income at screen printing cutting sanpas (study at the Assya'roniyyah Islamic boarding school). This research method uses a quantitative approach. The population in this study was an unlimited number of students at the As-Sya'roniyyah Islamic boarding school. The sampling technique used Purposive Sampling Technique, with the criteria being that respondents had made purchases at the screen printing cutting department at least twice, were at least 15 years old, male or female. The data collection technique is through distributing questionnaires to respondents who meet the criteria. The data analysis method used is simple Linear Analysis with the SPSS (Statistics Product and Service Solution) program version 25. The research results prove that sales volume does not have a significant effect on business income. However, simultaneously sales volume has a positive and significant effect on business income. The conclusions from this research prove that the more and higher the sales volume, the higher the business income in this research. Keywords: Sales Volume, Business Income, Islamic Boarding School